Organizations as human communities and internal markets: searching for duality - Cunha, M. P.; Rego, A.; Vaccaro, A. (Journal of Business Ethics, 2014)
Business firms have been explained as internal markets or as communities. To be sustainable, however, they need to reconcile these two constituting elements that have mainly been touted as opposite and part of a dualistic relationship. We suggest that organizations may, in alternative, view market and community as part of a duality, interdependent and mutually constituting processes that may not only contradict each other but also enable one another. The implications of a duality view for business ethics, which articulates market and community elements in a fruitful, mutually enabling relationship, are considered, and duality is presented as a way of transcending what is commonly viewed as opposition, moving organizations both in the direction of humane and competitive finalities